2017
DOI: 10.1177/1203475417745826
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Malodour in Quality of Life of Patients With Hidradenitis Suppurativa

Abstract: Malodour is a common symptom that significantly impairs quality of life in patients with HS. The fact that this effect is captured in Skindex and not the DLQI may be attributed to the nonspecificity of the DLQI in terms of unique disease characteristics. It is important to address odour in the management of patients with HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 18 publications
1
50
0
1
Order By: Relevance
“…Amino acid metabolism may impact body odor and skin pH. Malodor significantly impairs the quality of life in HS patients (Alavi et al 2018). The breakdown of isoleucine to isovaleric acid contributes to "sour" odor (Lam et al 2018), and we identified altered isoleucine biosynthesis and degradation pathways in HS skin.…”
Section: Discussionmentioning
confidence: 71%
“…Amino acid metabolism may impact body odor and skin pH. Malodor significantly impairs the quality of life in HS patients (Alavi et al 2018). The breakdown of isoleucine to isovaleric acid contributes to "sour" odor (Lam et al 2018), and we identified altered isoleucine biosynthesis and degradation pathways in HS skin.…”
Section: Discussionmentioning
confidence: 71%
“…Profound impact on the HRQoL of Irish HS patients was reported, including diminished work productivity and various psychological comorbidities . The severity of odour in HS patients was associated with total Skindex‐29 scores but not with DLQI scores . In an international study of the QoL impact of treatment (the last DLQI item), over half of HS patients reported problems .…”
Section: Resultsmentioning
confidence: 99%
“…83 The severity of odour in HS patients was associated with total Skindex-29 scores but not with DLQI scores. 84 In an international study of the QoL impact of treatment (the last DLQI item), over half of HS patients reported problems. 85 The relationship of serum zinc levels with QoL and disease severity in HS was studied: low zinc levels were associated with DLQI !…”
Section: Validation Of Hs-specific Qol Instrumentsmentioning
confidence: 99%
“…Pain and discomfort had the most significant impact on the index. Vinding et al (16) found a mean EQ-5D index of 0.82 (95% confidence interval (CI): 0.74--0.90) and a mean VAS score of 79.56 (95% CI: 72.89-86.22). It is speculated that the participants had less severe disease than those in the present hospital-based study because they were drawn from the general population.…”
Section: Hospital-based Studies Of Hr-qol In Hidradenitismentioning
confidence: 99%
“…There was no difference in mean DLQI scores for the low-vs highodour groups, but patients with high odour had a greater quality of life impairment as measured by the Skindex tool (t = −4.19, df = 43, P < 0.0001, mean difference = −18.87). 16 In an interesting probe of the impact of HS on body image researchers in Germany using the Frankfurt Body Concept Scale found that HS significantly reduced body image (mean FKKS score, 234.2 [5.4] in patients and 276.9 [5.7] in controls; P < 0.001), even when controlled for BMI. 17 A correlation was found for the extent of body image disruption and BMI (r = −0.589; P < 0.001), HADSdepression score (r = −0.619; P < 0.001), and HADSanxiety score (r = −0.340; P = 0.03).…”
Section: Hospital-based Studies Of Hr-qol In Hidradenitismentioning
confidence: 99%